Preparation and application of supermolecule polymer framework material - ZHANG YOUMING; LIN QI; ZHONG KAIPENG; CHEN XIAOPENG; LI YONGFU; YAO HONG; WEI TAIBAO (2018)
The invention designs and synthetizes a supermolecule polymer framework material. The supermolecule polymer framework material is formed through self assembly in cyclohexanol by using naphthalimide functionalized pillar [5] arene as a subject and bilateral quaternization pillar [5] arene as an object, wherein the mole ratio of the subject to the object is 1:1. Through competitive coordination mechanism, the supermolecule polymer framework material (SOF-AP5-MJP5) and a metal supermolecule polymer framework material (M-SOF-AP5-MJP5) can respectively realize continuous response and high-sensitivity detection to Fe<3+> and H2PO4<->; the recognition performance has important application values in the field of ion recognition. 本发明设计合成了种超分子聚合物框架材料，是以萘二甲酰亚胺功能化的柱[5]芳烃为主体，含有双边季铵化的柱[5]芳烃为客体，在环己醇中自组装而成，并且主体与客体的摩尔比为1:1。通过竞争性配位机理，这种超分子聚合物框架材料（SOF-AP5-MJP5）及其金属超分子聚合物框架材料（M-SOF-AP5-MJP5）能够分别对Fe和HPO实现连续性响应和高灵敏检测，这种识别性能在离子识别领域具有重要的应用价值。